BACK-END DESIGN OF A WEBSITE-BASED E-COMMERCE U-MARKET USING THE LARAVEL FRAMEWORK WITH THE SCRUM METHOD - Annisa Tri Hapsari (Universitas Lampung, 2026)
This research focuses on back-end development, including the management of user, product, and transaction data through a structured REST API. The Scrum method is applied to support iterative and incremental system development through 4 stages of sprints, allowing each feature to be developed, tested, and evaluated progressively. System testing is conducted using black box testing to ensure all functionalities operate as intended, and stress testing using Apache JMeter to evaluate system performance under concurrent user loads. The testing results indicate that all developed API endpoints function correctly and meet the defined testing scenarios. Furthermore, stress testing with varying loads of up to 300 samples demonstrates that the system maintains stable performance without significant failures, indicating that the back-end is capable of handling concurrent requests effectively. The implementation of core features, including user authentication, product management, shopping cart, transaction processing, and integration with the Midtrans payment gateway, operates as expected. Therefore, the U-Market system provides a more structured, secure, and efficient solution compared to the previous method, while the application of the Scrum method contributes to improving the effectiveness of the development process and the quality of the resulting system.